DEVELOPMENT OF SOFTSKILL-BASED VIDEO GAME LEARNING MEDIA FOR MUFRᾹDAT MASTERY IN JUNIOR HIGH SCHOOL LEARNERS - Ramlan, Ramlan; Syahril, Sulthan; Kesuma, Guntur Cahaya; Erlina, Erlina; Aridan, Muhammad (STIQ Amuntai, 2023)
This study aims to determine the development process, feasibility, response, and effectiveness of soft skills-based video game learning media in mastering mufrodat. This research is a type of development research (R&D). By using the five steps of the ADDIE development model, namely 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The data collection techniques used were interviews, observations, questionnaires and tests. The research data were analyzed quantitatively and qualitatively. This research results in a soft skill-based video game Learning Media for mufrodat acquisition. Based on the validation that has been done by material and language experts, media experts and 8th-grade Arabic teachers, the average score is 4.63 with the category